School administrator succession planning : identifying high-impact practices, programs, and frameworks in P-12 schools - Sabina, Lou L. (Emerald Publishing Limited : Information Age Pub., 2022)
"Across the United States and globally, school districts are regularly facing a shortage of both willing and highly-qualified candidates to assume positions as school leaders. A number of factors have contributed to this shortage including but not limited to: (1) retiring baby boomers leaving P-12 schools (ex. Aaronson & Meckel, 2009; Carlson, 2004; Parylo & Zepeda, 2015; Wiedmer, 2015), (2) shifting demographics and population changes across the United States workforce and schools (ex. Betts, Urias, & Betts, 2009; Brimley, Garfield, & Verstegen, 2005; Brown, 2016; Miller & Martin, 2015; Mordechay & Orfield, 2017), (3) increasing demands for school administrators making the position less desirable (ex. Grissom, Loeb, & Mitani, 2015; Lortie, 2009; Norton, 2002; Yan, 2019), and (4) the shift of schools to 21st Century Learning centers, which have changed the role of school administrators (ex. Crow, Hausman, & Scribner, 2002; Huber, 2014). According to the National Bureau of Labor Statistics, the current demand for school principals continues to increase (Occupational Outlook Handbook, 2019) and will accelerate in the coming 10-20 years. Because of the high need for school administrators, many schools and school districts are creating unique, targeted, and innovative programs to find principals who can meet the changing needs in our school system. For this edited volume, I invite chapter proposals from authors who are engaged in practices involved with succession planning for school administrators, either at the school level, district-level, or university level. Authors may submit proposals to discuss promising projects that have already been completed or that are currently in the proposal or early implementation phase. All proposals should clearly have a connection to some dimension of succession planning, whether it be implementation, design, partnerships, or specific practices to identify high-quality leadership candidates"--